Microarray analysis : biochips and eradication of all diseases - Sharma, Kal Renganathan (Biomedical engineering collection., 2015)
Microarray Analysis is a natural outgrowth of the author's teaching and research into the field of microarray processing, a fast growing and developing field. The book highlights the development of various microarray analysis tools and the applications of the technology towards disease prevention and eradication. The goal is to illustrate the many sequencing methods in place, and to show the various applications of these methods. This book will show how the biochemical reactions involved in the different steps of the cure process can be studied using microarray methods. Examples will be provided throughout the text of various disease states, including the spread of cystic fibrosis in children consanguineous marriages in Saudi Arabia, genetic disorders, and autoimmune disorders. The protocols from sample preparation to confocal scanning microscopy and detectors using photo multiplier tubes, biochip manufacturing methods, advances in sequencing methods, microfluids, electrophoretic methods are discussed in detail. The Polymerase chain reaction, a technique used to amplify and simultaneously quantify a targeted DNA molecule is explored. The criteria for choosing the best surface to use for microarray analysis is elloborated. Additionally, Microarray Analysis: Biochips and Eradication of Disease will feature the statistical methods needed for analysis of DNA data from microarray analysis, including shotgun and next generation sequencing.